Kohti yhteistä hyvää – Riippuvuussairaiden näkökulma päihdeongelmien tunnistamiseen ja hoitoon työelämän kontekstissa - Viitasaari, Maija; Järlström, Maria; Saru, Essi; Mäki, Elviira (Hallinnon tutkimuksen seura, 2025)
Common Good as an orientation in human resource management (HRM) research encourages organizations to partake in solving societal challenges. Substance dependence is one major societal challenge as approximately 10 percent of the working force is suffering from it. This study examines the manifestation and organizational responses to substance dependence in a work context and how the responses from organizations can contribute to the common good. Qualitative data (n=53) was collected via an online survey from current or recovering people with substance use disorder and analyzed using data-driven content analysis. The results indicate that the organizational manifestations, procedures and reactions in substance dependencies vary and include challenges, such as difficulties in identification and lack of knowledge. This study proposes a multilevel approach to common good HRM including common good principles and values.